Criterion of a relative estimation antideteriorat ionand antifrictional properties of lubricant materials - Мнацаканов, Р. Г.; Маленко, В. І.; Довбуш, В. О.; Микосянчик, О. О. (Proceedings of National Aviation University (archive), 2003)
In a paper the criterion of a relative estimation antideterioration and antifrictional properties of lubricant materials is described. The temperatures of lubricant environment, angular velocity for group of mineral oils are defined change of specific operation of abrasion in function of contact effort